2016
DOI: 10.1136/bcr-2016-215437
|View full text |Cite
|
Sign up to set email alerts
|

Congenital depression of the skull in a neonate

Abstract: Congenital depression of the fetal skull is a rare condition. We discuss the case of a 14-days-old male infant, born at term by elective non-complicated caesarean section presenting with a left temporoparietal skull depression. A CT scan was performed which showed no associated fracture. A conservative approach was followed since the infant showed no signs of neurological deficit. Similar cases have been managed successfully in other reports using a conservative approach, with the condition being often self-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…A depression linked to obstetric trauma is referred to ping-pong fracture of the skull, which presents in a similar manner. As our case was delivered uneventfully with no obstetric instrument usage and no crack or break line was not detected in the osseous indentation on CT, we diagnosed the patient as having a On a review of the available literature, congenital skull depression mostly occurred in the parietal bones and much less in the frontal bones; however, the mechanism is still unclear [1][2][3][4]. When compared to a depression in the hairy temporal area, a deformity in the bald frontal area disfigures the neonate's facial appearance and is conspicuous to people around.…”
Section: Discussionmentioning
confidence: 89%
“…A depression linked to obstetric trauma is referred to ping-pong fracture of the skull, which presents in a similar manner. As our case was delivered uneventfully with no obstetric instrument usage and no crack or break line was not detected in the osseous indentation on CT, we diagnosed the patient as having a On a review of the available literature, congenital skull depression mostly occurred in the parietal bones and much less in the frontal bones; however, the mechanism is still unclear [1][2][3][4]. When compared to a depression in the hairy temporal area, a deformity in the bald frontal area disfigures the neonate's facial appearance and is conspicuous to people around.…”
Section: Discussionmentioning
confidence: 89%
“…With regards to watchful waiting, there are no definite predictors to distinguish which fractures will elevate spontaneously. However, literature advises for a 6‐month observation period in the absence of neurological symptoms as most skull depressions resolve within 4 months 3–5 . Moreover, reviews such as Steinbok et al's analysis of 111 cases of paediatric depressed skull fractures demonstrated no differences in neurological or cosmetic outcomes between surgical and non‐surgical treatment in children with depressed skull fractures 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Treatment options include manual elevation via digital pressure at the fracture edges, suction elevation using a vacuum extractor or breast pump, surgical elevation and observation. Conservative management is advised in the absence of brain injury as the deformity will often correct itself as the skull grows over the following months 3 . Herein, we present a rare case of an infantile traumatic depressed skull fracture that spontaneously resolved within 4 hours of the injury.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…A number of published cases have demonstrated spontaneous resolution of the depression within 4 months without any cosmetic or neurodevelopmental sequelae [1][2][3][4]. However, all of these reports are for congenital skull depression on the parietal or temporal area and it is unclear whether the finding hold true for congenital frontal-vault depression.…”
Section: Discussionmentioning
confidence: 99%